Assessment of health and safety solutions at a construction site - Dėjus, Titas; Antuchevičienė, Jurgita (Journal of Civil Engineering and Management, 2013)
To design solutions for occupational safety at a construction site for the construction technology project, an occupational hazard was assessed. Possible solutions for occupational safety depend on the number of criteria such as hazardous factors from which workers must be protected; the number of danger zones; architectural-design and structural solutions of a building; types of technical protection measures, etc. A large set of solutions for occupational safety predetermines the number of respective typical (or repeated) solutions, which are based on specific technical safety measures and are applicable depending on a hazardous factor; besides, it determines systematisation of the solutions on these grounds. It is suggested to use the Multiple Criteria Decision Making (MCDM) technique for assessment and selection of appropriate solutions for occupational safety. The authors propose formulating assessed alternatives from the typical solutions to ensure their quality and then apply the entropy method for determining relative significances of evaluation criteria and, finally, use Weighted Aggregated Sum Product Assessment (WASPAS) method for ranking of alternatives.